The impact of breast cancer awareness campaigns on the knowledge, attitudes, and practices of breast cancer screening among Saudi female employees - Nada A. Alomairy (PLoS ONE, 2025)
Background Breast cancer (BC) stands as a significant and prevalent malignancy impacting women. The increase in statistics is primarily due to delayed detection, often attributed to a lack of awareness of symptoms. Additionally, emotional barriers and unfavourable attitudes toward breast screening contribute to the escalating prevalence of BC. This study targeted female university employees due to their dual role as professionals and caregivers, with a high potential for personal and community impact. This study aimed to evaluate the effectiveness of the university’s breast cancer (BC) health campaign related to the knowledge, attitudes, and practices (KAP) of female employees. Materials and methods A cross-sectional descriptive study was conducted in October and November 2023, following a BC awareness campaign. An online self-administered questionnaire was used to collect the data. The campaign, in the form of awareness, included posters, brochures, and lectures. The subjects were 290 female workers recruited from various departments of the university. Validation of the sampling and questionnaire, using a pilot test and reliability analysis, was conducted. Demographic data was analysed using frequency and percentage. Independent t-tests and one-way ANOVA were used to analyse the differences in knowledge and attitude towards breast cancer between various demographic variables. Results The results revealed that the health campaign significantly increased knowledge and fostered positive attitudes toward BC. Participants who had previously attended any prior BC health campaign scored higher in both knowledge (7.45 ± 0.98) and attitude (5.30 ± 1.48) compared to those who had never attended (knowledge: 6.10 ± 1.10, attitude: 4.10 ± 1.41). There were significant differences in the knowledge scores based on education level (p = 0.044), with participants with higher education having a higher mean knowledge score (7.50 ± 0.85) compared to those with a bachelor’s degree (6.70 ± 1.02). Participants with a family history of breast cancer had similar knowledge scores to those without but lower attitude scores. Independent t-tests and one-way ANOVA indicated that education level and attendance at the breast cancer health campaign were the significant factors associated with knowledge and attitude scores. Conclusion The findings show that there was a positive attitude towards BC. Nevertheless, additional interventions, such as counselling services and promoting available BC screening, must be added to facilitate screening behaviour. Future campaigns are also recommended to use diverse, culturally sensitive strategies targeting both younger and older women, as well as men.